2008
DOI: 10.1007/s12160-007-9010-y
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–Behavioral Stress Management Interventions for Persons Living with HIV: A Review and Critique of the Literature

Abstract: Background-Psychological adjustment and coping are central to human immunodeficiency virus (HIV) management. To improve HIV-infected patients' ability to cope with stress, a variety of stress management interventions have been designed and evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 62 publications
4
101
0
Order By: Relevance
“…The efficacy of group-based or individualized face to face CBI programs for people living with HIV have been shown by earlier studies [8][9][10][11][12]. The presents pilot study demonstrated that HIVpositive individuals who received a self-help program at their home address and worked on relaxation, cognitive change and life goals for 4 weeks, reported significantly fewer depressive symptoms after completion of the program, compared to people on a waiting list.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The efficacy of group-based or individualized face to face CBI programs for people living with HIV have been shown by earlier studies [8][9][10][11][12]. The presents pilot study demonstrated that HIVpositive individuals who received a self-help program at their home address and worked on relaxation, cognitive change and life goals for 4 weeks, reported significantly fewer depressive symptoms after completion of the program, compared to people on a waiting list.…”
Section: Discussionmentioning
confidence: 58%
“…The majority of these interventions employ cognitive-behavioral intervention (CBI) techniques (see review studies: [8][9][10][11][12]). Several review studies have been performed, showing that all programs involved group-based or individualized face to face contact, and consisted of multiple sessions [8][9][10][11][12]. Overall, psychological interventions for HIV-infected persons significantly improve mental health and quality of life [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings generally support the efficacy of psychotherapeutic interventions aimed at decreasing negative affect and increasing positive psychological resources among PLWH [46,47]; however, limitations like stringent inclusion criteria raise questions about the clinical utility or generalizability of such interventions [48]. Safren et al found that HIV-positive men and women who engaged in a 12-week CBT intervention period for adherence and depression reported reductions in depressive symptoms and greater adherence to electronically monitored anti-retroviral therapy (ART) compared to those who received a single session of intervention [49].…”
Section: Incorporating In-home Cbt To Treat Older Plwhmentioning
confidence: 85%
“…This review provides a summary of key findings from the previous narrative review and meta-analyses that have examined the efficacy of stress management interventions for PLWHA. [26][27][28] Next, the existing reviews are updated by highlighting recent stress management interventions designed to reduce psychological distress and improve coping skills among PLWHA. Specifically, this review describes core components of recent intervention approaches, reviews intervention efficacy findings, and offers guidance for future research.…”
Section: Introductionmentioning
confidence: 99%